Edukasi “Gadget sehat untuk anak hebat” dengan read-aloud dan permainan edukatif nondigital pada anak - Elisabeth Dwi Anggraeni; Ratri Sunar Astuti; Diana Permata Sari; Cecilia Paulina Sianipar; Trivena Cantika Stefani Soenarjo; Zefanya Putri Armanita (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2026)
Excessive gadget use in early childhood can negatively affect their motor, social, and emotional development. Based on a survey conducted at GKJ Condongcatur, 60% of parents reported signs of gadget dependency in their children, such as crying when the gadget was taken away and difficulty concentrating. The community service activity titled “Healthy Gadgets for Great Kids” aimed to increase Sunday School children’s understanding of healthy gadget use while encouraging active play and social interaction. The methods used included interactive education activities through read-aloud storytelling and educational games such as assembling puzzles, flashcards, daily schedule clocks, and playing “Simon Says”. The results showed children’s understanding of screen time limits, recognition of good and bad behaviors, and awareness of alternative activities such as outdoor play and helping parents. Children also demonstrated high enthusiasm and interaction with these educational activities. This program shows potential as a community education model to foster healthy digital awareness from an early age.